Peran Semantis Argumen Klausa Verbal Bahasa Dawan Dialek Amanuban, Nusa Tenggara Timur - Horiana Ilyadim Tenis; Yoseph B. Kroon; Johnson W. Haan (SASDAYA: Gadjah Mada Journal of Humanities, 2018)
This research entitled “The Role of Semantic Argument on Verbal Clauses of Dawan Dialect Amanuban”. The Problems discussed in this research are (a) How is the basic structure of verbal clause of Dawan Dialect Amanuban? (b) What role does the semantic argument contain in the verbal clause of Dawan Dialect Amanuban? The study aims to (a) Describe and analyze the structure of the verbal clause argument of Dawan Dialect Amanuban, (b) Identify and analyze the role of semantic argument verbal clause of Dawan Dialect Amanuban. The Method used is qualitative descriptive method and macro perceived theory (Macro rules). Based on this theory, the analysis of the research results shows that the basic structure of the BDDA verbal clause is Subject-Predicate-Object (SPO) and Subject-Predicate (SP) in the intransitive clause. Percent macro actors are realized through the thematic role of locative influencing agents, theme, instrumental, and benefactive. The role of the macro underground is realized through the thematic, benefactive, instrument, theme, locative, and influence roles.